Wayang Potehi at Hong San Kiong Temple in Gudo, Jombang, Indonesia: An Effort to Preserve the Culture and Religious Moderation - Masruroh, Sayidah Afyatul (LP2M - Universitas Islam Negeri Walisongo Semarang, 2023)
Indonesia’s rich cultural and religious diversity offers a unique context to explore how traditional arts contribute to social harmony. This article examines the Wayang Potehi performance at the Hong San Kiong Temple in Gudo, Jombang, and its role in promoting religious moderation. It highlights how performing arts are an inclusive platform that celebrates cultural and religious diversity, fostering tolerance and coexistence. The Hong San Kiong Temple, as a center for religious and cultural activities, provides an ideal setting to observe the integration of traditional arts like Wayang Potehi in pluralistic societies. The research uses a qualitative approach, including participatory observation, interviews, and document analysis, to understand how religious moderation is reflected in the performances. Findings indicate that Wayang Potehi conveys messages of moderation through its themes and the interaction between performers and audiences. These performances emphasize inclusivity, tolerance, and respect for diverse cultures and religions. The Hong San Kiong Temple’s efforts to promote religious moderation through these arts highlight a positive initiative that brings together diverse communities. This article offers valuable insights into how traditional arts can foster religious moderation and underscores the potential of performing arts in religious spaces to bridge divides in multicultural societies.